EFEKTIFITAS KELAS IBU HAMIL MELALUI APLIKASI WHATSAPP TERHADAP PENGETAHUAN TENTANG BAHAYA KEHAMILAN - Yesi Ari Sonaidah (Akademi Kebidanan SEMPENA NEGERI Pekanbaru, 2022)
ABSTRACT Since the Covid 19 pandemic, class activities for pregnant women cannot be carried out. but can take advantage of current technology, for example whatsaapp. This study aims to determine The Effectiveness of Pregnant Women’s class through Whatsapp Application in Improving Mother's Knowledge About the Hazard Signs of Pregnancy in the Work Area of Sidomulyo Outpatient Community Health Center in 2020. This research is quantitative with quasi experimental designs, with Two group pre-test post test design. The population in the research was 94 primigravida mothers. The sample consist of 15 people in control group and experimental group. Technique of analysing data by using Wilcoxon and Mann Whitney.The results of control group’s dependent T-Test obtained that pre-test average value was 6.07 and post test was 7, 73 with Pvalue 0.157 it is means that there is no influence of knowledge before and after intervention. Then the experimental group’s pre-test average score was 6.40 and post test was 11, 67 with Pvalue 0.008, which means that there is an influence of knowledge before and after intervention. Based on the results of the Independent T-Test, the value of Pvalue was 0.002, which means that there was a significant difference between experimental group and control group after the intervention It is recommended to health workers, especially midwives, develop learning media to increase knowledge from classical methods to blanded methods Key word : Knowledge, Effectiveness, Classes for Pregnant Wom, Whatsapp Application ABSTRAK Semenjak pandemi Covid 19 kegiatan kelas ibu hamil tidak dapat dilaksanakan, namun bisa memanfaatkan tekhnologi pada saat ini misalnya whatsaapp. Penelitian ini bertujuan untuk mengetahui Efektifitas Kelas Ibu Hamil Melalui Aplikasi Whatsapp Terhadap Peningkatan Pengetahuan Ibu Tentang Tanda Tanda Bahaya Kehamilan Di Wilayah Kerja Puskesmas Sidomulyo Rawat Jalan Tahun 2020. Penelitian ini bersifat kuantitatif dengan Desain eksperimen semu atau quasi experiment designs, dengan rancangan Two group pretest posttest. Populasi dalam penelitian berjumlah 94 ibu primigravida, Sampel berjumlah 15 orang kelompok kontrol dan kelompok eksperiment. Analisa data menggunakan uji Wilcoxon dan Mann WhitneyHasil uji dependent T-Test pada kelompok kontrol di dapatkan nilai rata – rata pretest 6,07 dan posttest 7, 73. Dengan nilai Pvalue 0,157 yang berarti tidak ada pengaruh pengetahuan sebelum dan sesudah intervensi. Kelompok eksperiment di dapatkan nilai rata – rata pretest 6,40. Dan posttest 11, 67. Dengan nilai Pvalue 0,008 yang berarti ada pengaruh pengetahuan sebelum dan sesudah intervensi. Berdasarkan hasil uji Independent T-Test diperoleh nilai Pvalue 0,002 yang artinya ada perbedaan yang signnifikan anatara kelompok eksperimen dengan kelompok kontrol setelah dilakukan intervensi. Disarankan kepada tenaga kesehatan terutama bidan melakukan pengembangan media belajar untuk meningkatkan pengetahuan dari metode klasikal ke metode blanded.